Pembesaran Gingiva Pada Pengguna Alat Ortodonti Cekat: Literature Review - Danti Narulita; Vera Megawati (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2023)
Orthodontic tooth movement occurs due to tissue remodeling. The success of orthodontic treatment is affected by the strength of periodontal health, oral hygiene, and orthodontics. Users of orthodontic appliances have to maintain oral hygiene to avoid periodontal disease. The purpose of this study was to evaluate and review enlargement gingiva in orthodontic user. This literature review was conducted by searching for journals, case reports and research with the keywords "gingival enlargement", "fixed orthodontics" and "orthodontic mechanics". Research articles and their full texts can be accessed over a 10- year starting from 2011 to 2021. Based on this literature study, poor oral hygiene during orthodontic treatment cause complications in periodontal tissues. Orthodontic appliances in oral cavity affect biofilm accumulation and bacterial colonization and patients with periodontal tissues are more susceptible to swelling and bleeding. Gingival treatment includes surgical and non-surgical gingivectomy. Surgical treatment are conventional surgery (scalpel), electrosurgery (cautery), diode laser and chemosurgery. Non- surgical treatment after orthodontic treatment was completed there was oral hygiene instructions, scaling and root planning, the using of a toothbrush and interproximal treatment and recall scheduled.